Pojok Bermain Sebagai Media Pemberdayaan Untuk Mengurangi Ketergantungan Anak Pada Gawai - Indiyani Indiyani; Muhamad Luthfi Maulana; Nastiti Novitasari; Nisrina Nur Fadia; Raihan Fitriana; Reziana Maeza (LPPM Universitas Trunojoyo Madura, 2022)
The rapid development of technology is certainly very helpful in fulfilling life in various fields. However, this can have a negative impact if not used properly, especially for children. With the advancement of technology, many children are more focused on gadgets and tend to forget our culture, one of which is traditional games. In addition to the development of the times, the existence of a pandemic that requires children to study remotely, this can result in a lack of motivation to learn and children become dependent on gadgets. Based on this, we have succeeded in creating a community empowerment program, namely Play Corner which aims to create a fun learning atmosphere interspersed with traditional games to foster their love for learning, their love for traditional game arts, and love for each other without intermediary devices. In this case, considering that traditional games have their own uniqueness and characteristics, there will be an instillation of values and characters in them. The method used in this program is to provide socialization, training, and calistung coaching to children. The results of this program increase children's learning motivation, children can maximize their free time by reviving traditional games, this of course can reduce the use of gadgets in children.